De oauktoriserade migranterna i svensk byggnadssektor: En studie i deportationspolitik 1990–2004 (Sociologisk Forskning, 2009)
The unauthorized migrants in the Swedish construction sector – a study in the policy of deportation 1990–2004The unauthorized migration of construction workers to Sweden increased during the 1990s, especially at the end of the decade. The migrants often came from Poland and the Baltic states. The aim of this article is to examine this change of the migration pattern to Sweden and how the Swedish Building Workers Union responded to this new situation. I examine how the Building Workers Union cooperated with the Police authorities to find, capture and deport unauthorized migrants. A conclusion is that the Building Workers Union has not adopted a more inclusionary strategy towards unauthorized migrants, as have trade unions in Spain and US. The main strategy has instead been to try to restrict this migration. One explanation of this is that the Building Workers Union is a strong and well organized trade union. It didn’t perceive of unauthorized migrants as potential new members, but as a threat to wages and work conditions. Another explanation is that it has been able to restrict migration in the past. This may contribute to making demands for restrictions an attractive strategy in the present even when the possibilities of succeeding with this have diminished.
Keywords: unauthorized migrants; undocumented migration; migration policy; trade union; construction